Neuroimaging of Childhood Epilepsy: Focal versus Generalized Epilepsy - Assadsangabi, Reza; Ozturk, Arzu; Kantamneni, Trishna; Azizi, Nazarin; Asaikar, Shailesh M.; Hacein-Bey, Lotfi (Journal of Pediatric Epilepsy, 2021)
Neuroimaging plays an increasingly crucial role in delineating the pathophysiology, and guiding the evaluation, management and monitoring of epilepsy. Imaging contributes to adequately categorizing seizure/epilepsy types in complex clinical situations by demonstrating anatomical and functional changes associated with seizure activity. This article reviews the current status of multimodality neuroimaging in the pediatric population, including focal lesions which may result in focal epileptic findings, focal structural abnormalities that may manifest as generalized epileptiform discharges, and generalized epilepsy without evidence of detectable focal abnormalities.
Keywords: epilepsy; seizure; focal; generalized; childhood; magnetic resonance imaging